Participation in Decision-Making, Career Development, and Organizational Commitment - Ichdan, Dany Amrul; Maryani, Maryani; Yuliansyah, Yuliansyah (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 18 No 2 (2023), 2023)
Employee participation in decision-making is a key factor in an organization's success, significantly influencing career development and organizational commitment. This study underscores the ethical and strategic imperative for management to empower employees in decision-making processes, a vital component of human resource management. Focusing on municipal officers from the Lampung regional province, the research employed a survey method to gather data. Analysis of 70 valid responses using SmartPLS software highlighted the substantial impact of budgetary participation on both career development and organizational commitment. Moreover, the findings revealed a direct correlation between budgetary participation and organizational commitment. Employees involved in budgetary decisions demonstrated greater dedication to fulfilling the organization's objectives. The study emphasizes the significance of involving employees in budgetary decision-making processes, which directly affects career progression and commitment to the organization. Contributing to the expanding body of literature on budgetary participation in the public sector and emerging economies, this research offers insightful implications for organizations and managers aiming to enhance employee engagement and loyalty. Keywords: career development, emerging countries, organizational commitment, participation in decision-making, public sector